Effect of Herbomineral Preparation and their Corresponding Metal Nanoparticle on Enzymatic Activity and Growth Pattern of Baker’s Yeast - Sudheesh, Dr. M. S. (Asian Journal of Pharmaceutics (AJP), 2019)
In modern medicine, heavy metals are thought to be existing toxic and trace amount of metals such as lead and mercury is a regulatory concern in drug development and approval process. However, metals are an integral part of Indian traditional medicine Ayurveda and have a safe history of usage for the past 5000 years. Bhasma, which is a herbomineral preparation containing heavy metals are subjected to heat, pressure and is heated with herbal juice and this process for detoxification of metals as claimed by Ayurveda. The objective of the present investigation is to understand the physiochemical changes in metal due to Sodhana and impact on bio-molecules such as enzyme and eukaryotic cells. Bhasma is compared with nanoparticles of the same metal to study the effect of Sodhana on biocompatibility of metal nanoparticles. The basic aim of this research was to find out the ill effect of such metallic preparation (Mandur bhasma) used in Ayurvedic medicine system and their corresponding iron nanoparticles using Baker’s yeast (Saccharomyces cerevisiae) and biological enzymes. For the study, initially culture Baker’s yeast was prepared in the pre-sterilized yeast extract, peptone, dextrose media. Growth and morphological change in baker’s yeast cell was studied in the presence of the marketed ayurvedic formulation and its corresponding metal nanoparticles. At a similar time, standard microbiological assay procedures were also performed to find out the impact of these preparations on growth and morphology of yeast cells. An enzyme blocking study using the enzymes was also performed. Results showed that the iron nanoparticles (in higher concentration) have an inhibitory effect on the growth of yeast cells in comparison to the respective formulation. At the same time, the yeast cells show aggregation behavior and damaging with the abnormal surface in case of metallic nanoparticles. Effect on enzymatic activity was also found significant. On the basis of the present study it could be concluded that metals present in the ayurvedic preparations in Sodhit form do not have any objectionable behavior but there are certain need of pharmacovigilance to follow standard protocol to establish the safety and efficacy of such Ayurvedic preparations, and before coming to any final conclusion, still number of studies will also be needed.